SISTEM PENDUKUNG KEPUTUSAN PEREKRUTAN ANGGOTA BEM MENGGUNAKAN METODE SAW DAN TOPSIS - Aziza Najar; Volvo Sihombing; Musthafa Haris Munandar (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
This study aims to solve problems in the recruitment of prospective BEM members at Labuhan Batu University. To select a competent member of the Labuhan Batu University Student Executive Board (BEM) organization, several stages of selection were carried out. However, decision making in recruitment is prone to collusion and nepotism at the student level on campus. To overcome this, a decision support system (DSS) for the recruitment of BEM members was designed using the SAW and TOPSIS methods. The DSS is designed using criteria, namely: GPA, Interview Score, Support Certificate, Organizational Experience and Commitment with weights for each criterion are 10, 20, 20, 30, 30.The result of this study is a decision support system using the TOPSIS method and SAW. The two best alternatives obtained from the ranking results using these two methods are alternatives with numbers A7 and A8.